COMPOUND SENTENCE FOUND IN THE JUNGLE BOOK NOVEL BY RUDYARD KIPLING - Parwata, Komang Agus; Putra, I Gusti Bagus Wahyu Nugraha; Maharani, Putu Devi (Journal of Language and Applied Linguistics, 2021)
The purpose of this research is to find out the types of compound sentence in The Jungle Book novel by Rudyard Kipling. The data of this study were taken from The Jungle Book novel by Rudyard Kipling.  The theory used in this research is the theory from Oshima & Hogue (1998) about types of compound sentence which consist of compound sentence formed by coordinator, semicolon, and conjunctive adverb. Then to analyse the types of compound sentence the qualitative strategy is used. The result of the research shows that in The Jungle Book novel by Rudyard Kipling 85, the data found were divided into three types of compound sentence. They are compound sentence formed by coordinator, compound sentence formed by semicolon, and compound sentence formed by conjunctive adverb.